PENGARUH STRES KERJA, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI BAGIAN KEUANGAN DI KOTA BENGKULU - Saputra, Ade Tri; Fadli, Fadli (UNIB Press, 2017)
This research is a quantitative study that aims to examine the effect of work stress, work discipline, and motivation on the performance of financial officers.The sample in this study were employees / financial officials in Bengkulu City with a total sample of 56 respondents. The data used in this study are primary data obtained by distributing questionnaires to respondents. Hypothesis testing in this study used Multiple Linear Regression Analysis with the help of the SPSS version 16 program and a significance level of 5%.The test results show that 1) there is a significant effect of work stress on the performance of financial officers, 2) there is a significant effect of work discipline on the performance of financial officers, 3) there is a significant effect of work motivation on the performance of financial officers. financial officer performance.